2017
DOI: 10.1021/acssuschemeng.7b02790
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Depolymerization of Lignin and Woody Biomass in Supercritical Ethanol: Influence of Reaction Temperature and Feedstock

Abstract: The one-step ethanolysis approach to upgrade lignin to monomeric aromatics using a CuMgAl mixed oxide catalyst is studied in detail. The influence of reaction temperature (200–420 °C) on the product distribution is investigated. At low temperature (200–250 °C), recondensation is dominant, while char-forming reactions become significant at high reaction temperature (>380 °C). At preferred intermediate temperatures (300–340 °C), char-forming reactions are effectively suppressed by alkylation and Guerbet and este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 63 publications
3
78
1
Order By: Relevance
“…Lignin depolymerization into smaller, aromatic molecules, often requires solvents, catalysts, and hydrogen for deoxygenation. Solvents including methanol [6][7][8] ethanol [3,[9][10][11] ethanol/water 1 3 [12,13] methanol/water [14] propanol [15] or dioxane [16,17] have been investigated in detail as a medium for tandem solvolysis and hydrogenolysis reactions. These latter reactions can be catalyzed both by transition (Pt, Pd, Ru, Rh, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin depolymerization into smaller, aromatic molecules, often requires solvents, catalysts, and hydrogen for deoxygenation. Solvents including methanol [6][7][8] ethanol [3,[9][10][11] ethanol/water 1 3 [12,13] methanol/water [14] propanol [15] or dioxane [16,17] have been investigated in detail as a medium for tandem solvolysis and hydrogenolysis reactions. These latter reactions can be catalyzed both by transition (Pt, Pd, Ru, Rh, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In most of the aforementioned literature, the lignin-tosolvent ratios going into the reactor were chosen between 1:30 and 1:60 w/v, with higher lignin loadings generally manifesting in prohibitively high char formation and/or low conversion towards mono-aromatics [3,6,7,[9][10][11][12]. Here, we refer to our early work as a case in point, wherein we demonstrated an effective approach for lignin depolymerization to mono-aromatics in supercritical ethanol, using a Cu-Mg-Al mixed oxide catalyst [3,[9][10][11]. In this work, a high solvent to lignin ratio was used with the aim to obtain a high yield of lignin monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the repolymerization via the phenolic hydroxyl groups, the authors suggested that ethanol not only acts as a hydrogen-donor solvent, but also as a capping agent and formaldehyde scavenger, as shown in Figure 10 [121,123]. In a following paper, they discussed the influence of reaction temperature on the products [124]. At lower temperatures in the range of 200-250 • C, recondensation reactions are dominant whereas at higher temperatures of 380-420 • C, the char formation due to carbonization played a major role.…”
Section: Soda Ligninsmentioning
confidence: 99%
“…Simple noncatalytic solvolysis of biorefinery lignin in supercritical ethanol can produce a heptane soluble bio-oil without the need for the addition of a catalyst or a reducing agent [257]. The catalytic ethanolysis of lignin proposes the use of different catalysts: precious group metals (Pd, Pt, Ru, Rh …) and more abundant metals (Cu, Ni, Mo …) supported over oxides (alumina, ceria, zirconia, magnesia …) have been frequently reported [258][259][260][261], but alternative catalysts have been tested as well, such as silicon carbon nanoparticles [262] or ionic liquids [263]. Methanol have replaced ethanol in aqueous mixtures for lignin solvolysis with very similar results [264], while propanol and butanol have also been proposed [265].…”
Section: Liquefaction (Solvolysis)mentioning
confidence: 99%
“…. ) have been frequently reported [258][259][260][261], but alternative catalysts have been tested as well, such as silicon carbon nanoparticles [262] or ionic liquids [263]. Methanol have replaced ethanol in aqueous mixtures for lignin solvolysis with very similar results [264], while propanol and butanol have also been proposed [265].…”
Section: Liquefaction (Solvolysis)mentioning
confidence: 99%